Evidence from the 'PROspective MulticEnTer RadIcal Cystectomy Series 2011 (PROMETRICS 2011)' study: how are preoperative patient characteristics associated with urinary diversion type after radical cystectomy for bladder cancer? - Schmid, Marianne; Rink, Michael; Traumann, Miriam; Bastian, Patrick J.; Bartsch, Georg; Ellinger, Jörg; Grimm, Marc-Oliver; Hadaschik, Boris; Haferkamp, Axel; Hakenberg, Oliver W.; Aziz, Atiqullah; Hartmann, Florian; et al. (Annals of surgical oncology, 2015)
PURPOSE: The aim of this study was to examine preoperative patients' characteristics associated with the urinary diversion (UD) type (continent vs. incontinent) after radical cystectomy (RC) and UD-associated postoperative complications. - MATERIALS: In 2011, 679 bladder cancer patients underwent RC at 18 European tertiary care centers. Data were prospectively collected within the 'PROspective MulticEnTer RadIcal Cystectomy Series 2011' (PROMETRICS 2011). Logistic regression models assessed the impact of preoperative characteristics on UD type and evaluated diversion-related complication rates. - RESULTS: Of 570 eligible patients, 28.8, 2.6, 59.3, and 9.3% received orthotopic neobladders, continent cutaneous pouches, ileal conduits, and ureterocutaneostomies, respectively. In multivariable analyses, female sex (odds ratio [OR] 3.9; p = 0.002), American Society of Anesthesiologists score ≥3 (OR 2.3; p = 0.02), an age-adjusted Charlson Comorbidity Index ≥3 (OR 4.1; p < 0.001), and a positive biopsy of the prostatic urethra in the last transurethral resection of the bladder prior to RC (OR 4.9; p = 0.03) were independently associated with incontinent UD. There were no significant differences in 30- and/or 90-day complication rates between the UD types. Perioperative transfusion rates and 90-day mortality were significantly associated with incontinent UD (p < 0.001, respectively). Limitations included the small sample size and a certain level of heterogeneity in the application of clinical pathways between the different participating centers. - CONCLUSIONS: Within this prospective contemporary cohort of European RC patients treated at tertiary care centers, the majority of patients received an incontinent UD. Female sex and pre-existing comorbidities were associated with receiving an incontinent UD. The risk of overall complications did not vary according to UD type.